Impact Of Language Barriers And Financial Constraints On Visual Rehabilitation Access Among Low Vision Patients In Kolkata - Chattopadhayay, Shouvik; Tripathi, Himanshu; Mondal, Biswajit; Mishra, Neeta; Gite, Amol Rajendra (Journal of Neonatal Surgery, 2025)
Low vision presents a significant public health concern in India, particularly in urban contexts like Kolkata were socio-economic disparities complicate access to rehabilitation. Despite the availability of tertiary eye care services, many patients continue to face substantial barriers to functional recovery. This study aimed to assess the challenges encountered by low-vision patients in accessing visual rehabilitation, with a specific focus on the roles of language barriers and financial constraints. A cross-sectional, descriptive survey was conducted among 461 individuals identified as low-vision patients within the Kolkata metropolitan area. Data were collected using a structured questionnaire covering demographic details, psychosocial factors, and perceived barriers. Quantitative analyses included frequency distributions, chi-square tests, correlation matrices, and linear regression modelling. Results revealed that financial constraints and language mismatches significantly hinder access to low-vision devices and services, and both were found to be strong predictors of depression and anxiety. Regression analysis showed financial barriers had the highest impact on depressive symptoms (B = 0.3866, p < 0.001). The findings underscore the urgent need for integrated, multilingual, and economically inclusive rehabilitation policies. Addressing both structural and psychosocial dimensions of care is essential for building equitable low-vision support systems in India.